The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1208/s12249-020-01648-6
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilisation Improves Bioactivity and Stability of Insulin-Loaded Polymeric-Oligonucleotide Nanoparticles for Diabetes Treatment

Abstract: The oral bioavailability of therapeutic proteins is limited by the gastrointestinal barriers. Encapsulation of labile proteins into nanoparticles is a promising strategy. In order to improve the stability of nanoparticles, lyophilisation has been used to remove water molecules from the suspension. Although various cryoprotections were employed in the preparation of lyophilised nanoparticles, the selection of cryoprotectant type and concentration in majority of the developed formulation was not justified. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 79 publications
(180 reference statements)
0
14
0
Order By: Relevance
“…As chitosan has various beneficial effects on human health, for instance, in bone healing [ 48 , 49 ], it makes it quite an ideal biomaterial to employ in the drug delivery research sector. Various labs, including ours [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], have shown that chitosan is capable of encapsulating various types of therapeutic agents such as small molecule drugs to exploratory biologicals such as proteins and even DNA in delivery platforms of various sizes. As chitosan can even be ingested with no complications, this fact further cements the usefulness of this biopolymer in drug delivery R&D. Chitosan NPs have been formulated in the past using various methods, not limited to complex coacervation [ 64 ] and ionotropic gelation [ 65 ], both simple enough to carry out in most labs.…”
Section: Chitosan—a Promising Biopolymer That Has Potential In Athero...mentioning
confidence: 99%
“…As chitosan has various beneficial effects on human health, for instance, in bone healing [ 48 , 49 ], it makes it quite an ideal biomaterial to employ in the drug delivery research sector. Various labs, including ours [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], have shown that chitosan is capable of encapsulating various types of therapeutic agents such as small molecule drugs to exploratory biologicals such as proteins and even DNA in delivery platforms of various sizes. As chitosan can even be ingested with no complications, this fact further cements the usefulness of this biopolymer in drug delivery R&D. Chitosan NPs have been formulated in the past using various methods, not limited to complex coacervation [ 64 ] and ionotropic gelation [ 65 ], both simple enough to carry out in most labs.…”
Section: Chitosan—a Promising Biopolymer That Has Potential In Athero...mentioning
confidence: 99%
“…[43,205,216,217] Nanoparticles possess several favourable properties, including stability against enzymatic degradation, improved bioavailability and high carrier capacity. [218][219][220][221] One of the studies examined the antidiabetic effects of bioflavonoids-loaded nanoparticles on C2C12 cells and streptozotocin-induced diabetic rat model. [121] It was found that nanoparticles containing myricitrin (1, 3, and 10 mg/kg) could increase glycogen synthesis and its storage, GLUT-4 gene expression, glucose uptake and cell viability in C2C12 cells.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Coacervation has been widely used to produce polymeric nanoparticles [ 133 , 134 ] and was first used by Battaglia et al to prepare SLNs in 2010 [ 135 ]. This method is based on the acidification-induced precipitation of the alkaline salts of fatty acids.…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%